Effect of Chlorhexidine Treatment on Microleakage of Glass Ionomer, Giomer and Methacrylate-Based Composite Restorations in Class V Cavities - ŞENOL, AYŞE ASLI; TARÇIN, BİLGE; YILMAZ ATALI, PINAR (My University, 2024)
Purpose: The aim of this in vitro study was to evaluate the effects of three restorative materials and chlorhexidine digluconate (CHX) pretreatment on microleakage in Class V cavities. Materials and Methods: Thirty freshly extracted sound human molars were cleaned and stored in distilled water. Sixty standard Class V cavities were prepared on gingival 1/3 of buccal and lingual surfaces of each tooth. Teeth were randomly assigned into 3 groups corresponding to the selected restorative material (Fuji II LC Capsule/FC, GC; Beautifil Flow Plus/BF, Shofu; and GrandioSo Flow/GF, VOCO). Lingual cavities were pre-treated with CHX (Cavity Cleanser, Bisco). The cavities were restored according to manufacturer’s instructions using the materials’ own adhesive systems. Teeth were stored in distilled water (24°C) for 6 months for aging. Specimens were immersed in 2% methylene blue solution for 1 h and sectioned longitudinally in buccolingual direction. Occlusal/gingival margins were examined for dye penetration and scored under x8 and x20 magnification using stereomicroscope (Leica MZ7.5, Leica Microsystems). Statistical analysis was performed using chi-square test with a significance level of p<0.05. Results: There was no statistically significant difference between the amount of microleakage of GF, FC and BF restorations in CHX-treated and untreated cavities (p>0.05). CHX pretreatment did not result in a significant difference between microleakage values in gingival and occlusal margins of cavities restored with different materials (p>0.05). Conclusions: Application of CHX as cavity cleaner has no effect on the microleakage in Class V cavities restored with giomer, glass ionomer, and resin composites. Key words: chlorhexidine gluconate; composite resin; glass ionomer; microleakage
Keywords: Diş Hekimliği; Klinik Bilimler; Sağlık Bilimleri; Dentistry; Clinical Sciences; Health Sciences; Klinik Tıp (MED); Klinik Tıp; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Clinical Medicine (MED); CLINICAL MEDICINE; DENTISTRY, ORAL SURGERY & MEDICINE; Periodontoloji; Ortodonti; Ağız Cerrahisi; Diş Hijyeni; Dişçilik Hizmetleri; Diş Hekimliği (çeşitli); Periodontics; Orthodontics; Oral Surgery; Dental Hygiene; Dental Assisting; Dentistry (miscellaneous); General Dentistry; chlorhexidine gluconate; composite resin; glass ionomer; microleakage